Clinical indications for image-guided interventional procedures in the musculoskeletal system: a Delphi-based consensus paper from the European Society of Musculoskeletal Radiology (ESSR)-part V, knee - Sconfienza, Luca Maria; Adriaensen, Miraude; Albano, Domenico; Alcala-Galiano, Andrea; Allen, Georgina; Aparisi Gómez, Maria Pilar; Aringhieri, Giacomo; Bazzocchi, Alberto; Beggs, Ian; Chianca, Vito; Corazza, Angelo; Dalili, Danoob; et al. (Springer Science and Business Media LLC, 2022)
Interventional procedures around the knee are widely adopted for treating different musculoskeletal conditions. A panel of experts from the Ultrasound and Interventional Subcommittees of the European Society of Musculoskeletal Radiology (ESSR) reviewed the existing literature to assess the evidence on image-guided musculoskeletal interventional procedures around the knee, with the goal of highlighting some controversies associated with these procedures, specifically the role of imaging guidance, as well as the efficacy of the medications routinely injected.
Keywords: Interventional radiology; Knee; Patellar tendon; Platelet-rich plasma; Hyaluronic acid